CORRELATION BETWEEN TEACHER’S CARRACTER WITH STUDENTS’ LEARNING MOTIVATION IN TEACHING AND LEARNING PROCESS - Mul Muliadi; Majri Majri (BAHTRA : Pendidikan Bahasa dan Sastra, 2021)
This study aimed at knowing the correlation between the character of English teacher with the students’ learning motivation in teaching and learning process of eighth grade students of MTs NW Kalijaga. This study was designed as descriptive quantitative research and in collecting the data in this investigating the researcher used the non-test technique (questionnaire). The instrument (questionnaire) of data collection about the character of teacher and students’ motivation in teaching and learning process by using the scale which was prepared five answers alternatives are: score 5 for the students who answer solid (sangat setuju: SS), score 4 for the students who answer agree (setuju: St), score 3 for the students who answers uncertain (ragu-ragu: RG), score 2  for the students who answers disagree (tidak setuju: TS),  score 1  for the students who answers really disagree (sangat tidak setuju: STS). The result of the correlation computation by correlation between teacher’s character and students’ motivation in teaching learning process. The score obtained from the data analysis = 0,461, the score refer that the correlation was susfficient.